Assessing and Uplifting Sustainable Orality Languages in Nepal: A Case Study of Magar Kaike and Athpariya - Regmi, Dan Raj; Regmi, Ambika (Nepalese Linguistics, 2022)
Orality level of the languages of Nepal like Magar Kaike and Athpariya call for being evaluated within the FAMED conditions and community-based language development strategies have to be framed to increase the sustainable use of those languages from the perspective of Sustainable Use Model proposed in Lewis and Simons (2017).